Peptide PaDBS1R6 has potent antibacterial activity on clinical bacterial isolates and integrates an immunomodulatory peptide fragment within its sequence - Rezende, Samilla B.; Chan, Lai Yue; Oshiro, Karen G.N.; Buccini, Danieli F.; Leal, Ana Paula Ferreira; Ribeiro, Camila F.; Souza, Carolina M.; Brandão, Amanda L.O.; Gonçalves, Regina M.; Cândido, Elizabete S.; Macedo, Maria L.R.; Craik, David J.; et al. (Biochimica et biophysica acta. General subjects, 2024)
Resistant infectious diseases caused by gram-negative bacteria are among the most serious worldwide health problems. Antimicrobial peptides (AMPs) have been explored as promising antibacterial, antibiofilm, and anti-infective candidates to address these health challenges. Here we report the potent antibacterial effect of the peptide PaDBS1R6 on clinical bacterial isolates and identify an immunomodulatory peptide fragment incorporated within it. PaDBS1R6 was evaluated against Acinetobacter baumannii and Escherichia coli clinical isolates and had minimal inhibitory concentration (MIC) values from 8 to 32 μmol L−1. It had a rapid bactericidal effect, with eradication showing within 3 min of incubation, depending on the bacterial strain tested. In addition, PaDBS1R6 inhibited biofilm formation for A. baumannii and E. coli and was non-toxic toward healthy mammalian cells. These findings are explained by the preference of PaDBS1R6 for anionic membranes over neutral membranes, as assessed by surface plasmon resonance assays and molecular dynamics simulations. Considering its potent antibacterial activity, PaDBS1R6 was used as a template for sliding-window fr agmentation studies (window size = 10 residues). Among the sliding-window fragments, PaDBS1R6F8, PaDBS1R6F9, and PaDBS1R6F10 were ineffective against any of the bacterial strains tested. Additional biological assays were conducted, including nitric oxide (NO) modulation and wound scratch assays, and the R6F8 peptide fragment was found to be active in modulating NO levels, as well as having strong wound healing properties. This study proposes a new concept whereby peptides with different biological properties can be derived by the screening of fragments from within potent AMPs. [Display omitted] •PaDBS1R6 has a preference for Gram-negative bacterial membranes.•PaDBS1R6 showed a potent and fast bactericidal activity.•PaDBS1R6 undergoes a coil-to-α-helix transition in membrane-like environments.•PaDBS1R6 crosses outer membranes and ends up attached to inner membranes.•PaDBS1R6 has an immunomodulatory peptide encrypted within its sequence.